اثر المعنى في توجيه الاعراب عند ابن هشام الأنصاري (Journal of the College of Basic Education, 2022)
Many say: Arabic grammar is drowned in formalities and does not mean content with proverbsWhat is meant by form and pronunciation, and all that grammar does is study the verbal aspect and neglects one aspectthe meaning ; This is what avoids the fact that parsing is a grammatical function that cannot be taken withoutRefer to the meaning or connotation of the utterance, whether it is a grammatical device or a utterance affected by the presence of the agentGrammar (grammar is the law of composition of speech; and a statement of all that the word must be inSentence ; and sentence with camel; So that the phrase can be coordinated and can lead to its meaning (a) the purpose of grammarA statement of parsing and detailing its provisions; Until some of them called it (the science of parsing); the parsing is notparsing words; or just moving the end of the word; Rather, it is meant by the meaning that is understood by whomThe words and those who pointed out to that Abdul Qaher Al-Jurjani when he said (As for grammar, I thought it was a strike fromaffectation;